Pemberian Motivasi Dapat Meningkatkan Kinerja Karyawan Pada Pabrik Bakpia Patok 25 Yogyakarta - Muhamad Ma’ruf; Kristiana Sri Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
SDM becomes one of the important factors in determining the success of a company with the presence of work motivation, then the performance of employees will improve and the objectives of the company will be realized. The research was done at the Phathok 25 bakpia factory. Using a type of quantitative research method of saturated sampling with a questionnaire. The sample was given to the employees of the Bakpia Factory at the 25th grade with (X) motivation and (Y) performance. This study was analyzed using the IBM SPSS Statistics program 26. Results from the data processing of the study found that giving work motivation influenced the performance of employees who stated that the Validity Test and the Reliability Test had a fairly large cronbach alpha coefficient above 0.60. Whereas the correlation test 0.012 < of 0.05 then concluded there was a significant.